The Implementation Of Bumdes Based On Syariah In Developing Social Economy: A Case Study Of Bumdes In Rensing Bat - Safari, M. Ubaidillah Karomi (International Conference on Islamic Studies, 2020)
Abstract This study aims to determine the process of implementation and economic development of BUMDes based syariah. This study was a qualitative descriptive of BUMDes based on syariah in Rensing Bat. They were classified into two business categories such as agriculture and trade. Data were collected using observations, questionnaires, interviews and BUMDes’s data. This study revealed two results. First, the implementation of BUMDes based on syariah in Rensing Bat provides many choices of akad to society which were dominated by traders and farmers. The akad chosed including (a) the contract of deposit. (b) Profit Sharing consists of the Al-musyarakah, Al-mudharabah, Al-muzzara'ah, and Al-musaqah agreements. (c) Al-musyarakah. (d) Al-mudaraba. (e) Al-muzzara'ah. (f) Al-musaqah is. (g) Buying and selling consists of the Bai 'Al-murabahah, Bai' As-salam, and Bai Al-istishna contracts. (h) Dalambai 'Al-murabahah. (i) The Bai Al-istishna Agreement. (j) Lease or Al-ijarah Ijârah or lease. (k) Services consist of Al-wakalah, Al-kafalah contracts. Second, economy had gradually increasing in two business sectors they were trading and agricalture business. In the trading business unit could increase their product and trading class which from previously street vendors became traders in market shops, outlets and canteens. Beside, in agricultural business unit, there was an increasing in harvest yields farming such as rice, tobacco and chilli. Farmers maximize their yields to get more profit sharing. The capital obtained is used to buy good fertilizers, good irrigation work, selecting seeds quality to good care.